Analysis of the Use of Sand Pump Control Pumps in Overcoming Sand Problem in Sucker Rod Pump (SRP) in Sp Wells In the Kawengan Field - Sopacua, Putri (Journal of Petroleum and Geothermal Technology, 2024)
The sand problem is a common challenge in the oil and gas industry. PT Pertamina EP Asset 4 Cepu Field in the Kawengan Field has rock which is a ngrayoung formation and the type of sandstone can cause sand to enter into the well bour when oil is produced for a long time. Therefore, we need the right tool to be able to overcome the problem of sandiness. In this case PT Pertamina EP Asset 4 Cepu Field in the Kawengan Field uses a sand control pump in an effort to overcome the sand problem. Thus, this research was conducted by analyzing the appropriate pump size from the sand rate calculation, fluid flow rate before and after using the sand control pump, as well as economic analysis. The results of the pump size analysis show that the right pump size to use is 2 joint mud anchors. The results of the subsequent analysis show an increase in the rate of fluid production after using a sand control pump. The results of the economic analysis show that the use of a sand control pump on a sucker rod pump (SRP) in the SP well is feasible because it has economic value with an oil price of 45 US$ / bbl, an NPV of 221,709 USD is obtained, and project success (IRR) reaches 106 %, as well as the value of pay out time for 1.83 years. Keywords: Economy, Flow Rate, Sand Problem, Sand Control Pump, Sand Rate.